Initial witnessing on future witnessing: a mediation analysis of chronic community violence, posttraumatic stress, and delinquency in urban, African American youth - Wilkins, Kaleigh (Violence and victims, 2024)
Witnessing community violence can predict negative mental health outcomes for youth such as posttraumatic stress symptoms and delinquent behavior. Such outcomes differ by gender. Variables that predict witnessing community violence in youth are less understood. This study aims to explore potential pathways between initial witnessing and continued witnessing for early adolescents. The relationship between witnessing as a predictor and witnessing as an outcome is hypothesized to be mediated by both posttraumatic stress and delinquency and moderated by gender. A sample of 153 African American, sixth-grade students (M = 11.65, 59% female) in high-crime, high-poverty areas completed self-report surveys at baseline, 12 months, and 24 months. Moderated serial mediation was used to assess longitudinal associations. For the full model, delinquency at Time 3 was associated with a positive change in witnessing at Time 3. Gender moderated several paths. For girls, witnessing at Time 1 was predictive of high posttraumatic stress (aggregate) at Time 2 and high delinquency at Time 3. For girls, witnessing at Time 1 also was predictive of higher hyperarousal and higher intrusion subscale symptoms than other symptoms at Time 2. Analyses also indicated that hyperarousal at Time 2 significantly predicted witnessing at Time 3 for girls only. Finally, delinquency at Time 3 was associated with a positive change in witnessing at Time 3. For boys, no analyses indicated witnessing at Time 1 as a significant predictor. Results contribute to our understanding of the trajectory of witnessing community violence and the roles both posttraumatic stress subscales and delinquency play in that trajectory, especially among girls.